Recolección de germoplasma de frijol Phaseolus spp. L. en la región andina (centro de Colombia), Cundinamarca y Boyacá - Toro Chica, Orlando (International Center for Tropical Agriculture, 1992)
A five days collecting expedition was carried out through the Departments of Cundinamarca and Boyaca (Colombia), corresponding to the dry subtropical forest of the Andean Zone (1500-2000 m.a.s.l.). The germplasm collected includes 40 samples of beans of the genus Phaseolus, 1 sample of Vigna sp, and 1 sample of Centrosema sp.; these materials were not represented in the germplasm bank. The wild forms of P. vulgaris collected in these areas, show a wider variability, in terms of Phaseolin, compared with previous materials collected in the area; this finding will help to understand the evolutionary process of domestication/introduction of Phaseolus in the Andes of Colombia.